PENGARUH PERPUTARAN MODAL KERJA DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS (ROA) PADA PT. SIANTAR TOP TBK PERIODE 2014 – 2023 - Tyas, Titah Sekaring; Tua, Rudy Bodewyn Mangasa (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of working capital turnover and sales growth on profitability as measured by Return On Assets (ROA) at PT Siantar Top Tbk during the period 2014–2023. The data used are the company’s annual financial statements listed on the Indonesia Stock Exchange (IDX). The analysis method employed is multiple linear regression with the help of SPSS version 26 software. The results indicate that working capital turnover has a negative and significant effect on ROA, while sales growth does not have a significant effect on ROA. The coefficient of determination (Adjusted R Square) of 54.4% shows that variations in profitability can be explained by these two variables, while the remaining 45.6% is influenced by other factors outside this study. Therefore, PT Siantar Top Tbk needs to carefully manage its working capital to avoid reducing profitability and continue to improve operational efficiency to strengthen its financial performance